GEOINFORMATION TECHNOLOGIES IN THE MANAGEMENT OF THE DEVELOPMENT OF WATER SUPPLY AND WATER SUPPLY SYSTEMS - Kuznetsov, A.; Panov , V. (Pressing Problems of Public Administration, 2019)
The question of the possibility of introduction of geoinformation technologies in the management of the development of water supply and sewerage enterprises is analyzed. Geoinformation technologies are considered as a complex system aimed at forming mechanisms for managing sustainable functioning and balanced (reproducing) development of systems in conditions of negative natural and man-made factors. Based on the submitted data on water users, municipal water management system and other graphic information on territorial management, a rather large set of tasks is solved, in particular: development of environmental forecasts and programs for development of municipal water management; evaluation of large-scale projects and preparation of electronic environmental maps of the regions; the accumulation and processing of information about time-varying parameters for the purpose of environmental forecasting; working out of interstate conditions of interaction in border areas for the resolution of extreme environmental situations, including in emergency situations.